IMPLIKASI SHALAT DALAM MEMBENTUK KEPRIBADIAN PEREMPUAN - ‘Ulya, Fina (Sunan Kalijaga State Islamic University & The Asia Foundation, 2011)
The subject of women and the shalat is riddled with debate. In fiqh, certain arrangements are made that are subjective to men and women, the criteria for the imam or the placements of the rows for the prayer itself are such examples. Some feel that this is discriminatory towards women, while others feel that it is irrelevant to such cause. This article however, focuses more on the tasawuf aspect of shalat, which does not concern itself with matters practical or legal. It talks more on the essence, of how the shalat shapes, forms and ultimately influences one’s personality, this case the one being women in general.